2011
DOI: 10.3109/17549507.2011.604791
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality-of-life of children with speech and language difficulties: A review of the literature

Abstract: A review of the literature has been undertaken to examine health-related quality-of-life (HRQoL) of children and adolescents with speech and language difficulties (SaLD), with a particular focus on evidence regarding the domains of HRQoL most affected by SaLD. Twelve electronic databases were searched for articles on this topic published from 1966 to January 2011. Seven studies suitable for inclusion were identified. These papers were reviewed in relation to their participants, sample size, study design, and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 70 publications
4
38
0
1
Order By: Relevance
“…Studies focused on QoL in children with communication impairments, ranging in age from birth to 18 years, consistently find negative impacts on social functioning, e.g., difficulties getting along with others (Feeney et al . ), as well as difficulties in psychosocial well‐being and school functioning (Hubert‐Dibon et al . , McKean et al .…”
Section: Introductionmentioning
confidence: 99%
“…Studies focused on QoL in children with communication impairments, ranging in age from birth to 18 years, consistently find negative impacts on social functioning, e.g., difficulties getting along with others (Feeney et al . ), as well as difficulties in psychosocial well‐being and school functioning (Hubert‐Dibon et al . , McKean et al .…”
Section: Introductionmentioning
confidence: 99%
“…Early vocabulary skills are linked to communication development, including verb growth (Longobardi, Spataro, Putnick, & Bornstein, 2017), grammar (Bates & Goodman, 2001), and related skills, such as school readiness (Morgan et al 2015). Early language difficulties are related to a multitude of poor outcomes, including lower health-related quality of life (Feeney, Desha, Ziviani, & Nicholson, 2012), difficulties in social communication and personal relationships (Schoon, Parsons, Rush, & Law, 2010), poorer educational outcomes, and reduced career opportunities (Schoon et al, 2010). Studies have shown that children with language difficulties are also at increased risk for behavioral (Botting & Conti-Ramsden, 2000;Bretherton et al, 2014) and emotional difficulties (Goh Kok Yew & O'Kearney, 2015).…”
mentioning
confidence: 99%
“…Of particular relevance, Feeney et al . () discussed ‘ school functioning ’, the degree to which a child can participate in school, as being an important measure of outcome (table : 16). Such a perspective is aligned with those in the education literature about desired outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…In two further studies from SLTs, the importance of measuring outcomes more broadly are discussed, that is, the need to consider the wider impact of DLD on a child's quality of life (table 1: 16,23). Of particular relevance, Feeney et al (2012a) discussed 'school functioning', the degree to which a child can participate in school, as being an important measure of outcome (table 1: 16). Such a perspective is aligned with those in the education literature about desired outcomes.…”
Section: Achieving Desired Outcomes and The Nature Of Interventionmentioning
confidence: 99%